Dendritic cell-derived exosomes as maintenance immunotherapy after first line chemotherapy in NSCLC - Besse, Benjamin; Zörnig, Inka (OncoImmunology, 2016)
Dendritic cell-derived exosomes (Dex) are small extracellular vesicles secreted by viable dendritic cells. In the two phase-I trials that we conducted using the first generation of Dex (IFN-γ-free) in end-stage cancer, we reported that Dex exerted natural killer (NK) cell effector functions in patients. A second generation of Dex (IFN-γ-Dex) was manufactured with the aim of boosting NK and T cell immune responses. We carried out a phase II clinical trial testing the clinical benefit of IFN-γ-Dex loaded with MHC class I- and class II-restricted cancer antigens as maintenance immunotherapy after induction chemotherapy in patients bearing inoperable non-small cell lung cancer (NSCLC) without tumor progression. The primary endpoint was to observe at least 50% of patients with progression-free survival (PFS) at 4 mo after chemotherapy cessation. Twenty-two patients received IFN-γ-Dex. One patient exhibited a grade three hepatotoxicity. The median time to progression was 2.2 mo and median overall survival (OS) was 15 mo. Seven patients (32%) experienced stabilization of >4 mo. The primary endpoint was not reached. An increase in NKp30-dependent NK cell functions were evidenced in a fraction of these NSCLC patients presenting with defective NKp30 expression. Importantly, MHC class II expression levels of the final IFN-γ-Dex product correlated with expression levels of the NKp30 ligand BAG6 on Dex, and with NKp30-dependent NK functions, the latter being associated with longer progression-free survival. This phase II trial confirmed the capacity of Dex to boost the NK cell arm of antitumor immunity in patients with advanced NSCLC.
Gesehen am 07.05.2020